A survey of the Late Roman period (3rd-6th century AD): Pollen, NPPs and seeds/fruits for reconstructing environmental and cultural changes after the floods in Northern Italy. (2nd January 2019) - Bosi, G.; Labate, D.; Rinaldi, R.; Montecchi, M.C.; Mazzanti, M.; Torri, P.; Riso, F.M.; Mercuri, A.M.
Abstract: In this paper, we focus on the most critical but low-studied Late Roman phase (3 rd -6th century AD) of Mutina, an important Roman colony situated in Northern Italy. During this period, partly including the Late Antique, the seasonal variability with inconstant precipitation might have been responsible for devastating flood events. In the Po Plain, lying on four regions of Northern Italy (Piedmont, Lombardy, Emilia-Romagna and Veneto), an impressive set of flood events occurred that resulted in evident, sometimes thick sediment strata, in between the Roman archaeological layers, and after their full deposition. The research is a key example of integrated archaeobotanical analyses based on five archeological sites (on-site records) excavated within the modern city of Modena and studied for palaeoenvironmental reconstruction. Plant micro- and macro-remains were analysed in the framework of interdisciplinary archaeological studies, aiming at reconstructing the main floristic, vegetational and palaeoecological features of Mutina and its surroundings. Since early phases of the Roman age, there have been wetlands and thinly scattered mixed oakwoods that together with human environments, i.e. cereal fields and gardens, characterised the plant landscape of the area. Interestingly, during the Late Roman period, the woodland cover increased. Overall, the archaeobotany studies highlighted the effects of the floods on the city of Modena and its surroundings showing that subsequent episodes of floods favoured the expansion or spreading of wetlands with the development of hygrophilous woods in the later phases, after the flood of the 6th century AD.